Longer stent retrievers enhance thrombectomy performance in acute stroke. (1st June 2018) - Haussen, Diogo C; Al-Bayati, Alhamza R; Grossberg, Jonathan A; Bouslama, Mehdi; Barreira, Clara; Bianchi, Nicolas; Frankel, Michael R; Nogueira, Raul G
Abstract : Background: Longer stent retrievers have recently become available and have theoretical advantages over their shorter counterparts. We aim to evaluate whether stent retriever length impacts reperfusion rates in stroke thrombectomy. Methods: This was a retrospective analysis of a prospectively collected thrombectomy database in which equal diameter (4 mm) stent retrievers were used as the first-line strategy for intracranial internal carotid or middle cerebral artery M1 or M2 occlusions along with a balloon guide catheter from June 2011 to March 2017. The population was dichotomized into long (Trevo 4×30 mm/Solitaire 4×40 mm) or short (Trevo 4×20 mm/Solitaire 4×20 mm) retrievers. The primary outcome was first-pass modified Thrombolysis in Cerebral Infarction (mTICI) 2b/3 reperfusion. Results: Of 1126 thrombectomies performed within the study period, 420 were included. Age, gender, National Institutes of Health Stroke Scale, ASPECTS, IV tissue plasminogen activator use, stroke etiology, occlusion site, time from last-known-normal to puncture, distribution of Trevo and Solitaire, and the use of newer generation local thromboaspiration devices were comparable between the long and short retrievers. The short retriever group had more frequent hypertension, dyslipidemia, and atrial fibrillation. First-pass mTICI 2b/3 reperfusion was more common in the long retriever group (62% vs 50%; P=0.01). Parenchymal hematomas type 2, subarachnoid hemorrhage, 90-day modified Rankin Scale score 0–2, and mortality were comparable. Multivariable analysis indicated that long retriever (OR 2.2; 95% CI 1.3 to 3.6; P=0.001), radiopaque device (OR 2.1; 95% CI 1.2 to 3.4; P=0.003), and adjuvant local aspiration (OR 2.4; 95% CI 1.3 to 4.3; P=0.003) were independently associated with first-pass reperfusion. Conclusions: The use of longer stent retrievers is an independent predictor of first-pass mTICI 2b/3 reperfusion. First-pass reperfusion was also associated with the use of radiopaque devices and adjuvant local aspiration.